Clearing the road for high-fidelity fast ion simulations in full three dimensions. (December 2018) - Kurki-Suonio, T.; Särkimäki, K.; Varje, J.; Äkäslompolo, S.; Kontula, J.; Ollus, P.; Bécoulet, M.; Chôné, L.; Liu, Y.; Vincenzi, P.
Abstract : High-energy ions, such as fusion alphas and ions from external heating, can be very sensitive to any non-axisymmetric features in the confining magnetic field due to their collisionless nature. Since understanding the confinement properties of these ions is crucial for ITER (the first fusion reactor currently under construction in Cadarache, France) and beyond, it is of ultimate importance that the predictive simulations are accurate and free of numerical distortions. Adding the third dimension comes at substantial computational cost, calling for new kinds of approaches and computational platforms. In this contribution we discuss what new features, even new physics, the non-axisymmetry brings with it and how one could cope with the ever-increasing demands on both memory and CPU resources. In the end, a few simulation examples with a varying level of non-axisymmetry are given.